A PROJECT OF CONSTRUCTING A CONTEMPORARY JEWISH IDENTITY IN RABINOVICI’S NOVEL SUCHE NACH M - Liyanti, Lisda (UI Scholars Hub, 2019)
Attitude to the Nazi past turns to its new phase in the 1980s, after the time of repressing, silent and mourning brings the new discourse in talking about the Holocaust. It was a tendency of